Bio-sociological and clinical factors of chronic pain and pain interference in patients undergoing hemodialysis: a cross-sectional study - Bouchachi, Fatima Z.; AL Wachami, Nadia; Iderdar, Younes; Arraji, Maryem; Elgot, Abdeljalil; Chahboune, Mohamed (BMC nephrology, 2025)
Background End-stage kidney disease is an irreversible and incurable alteration of kidney function, requiring renal replacement therapy such as hemodialysis. Hemodialysis patients are one of the most symptomatic of all chronic kidney disease groups, including chronic pain. Overlooked, underestimated, and undermanaged, pain is associated with altered health-related quality of life. Therefore, this study aims to explore the biological, clinical, and social variables associated with chronic pain and its interference with hemodialysis patients. Methods A cross-sectional study was conducted on Moroccan hemodialysis patients. A total of 307 patients participated in the study. Data collection was based on a structured questionnaire with sociodemographic, clinical, and dialysis variables. The Numeric Rating Scale and Brief Pain Inventory were used to assess pain characteristics. Results Almost half of the hemodialysis had chronic pain, the mean pain severity and pain interference scores were 3.73 ± 3.59, and 22.89 ± 22.74 respectively. Multiple regression analysis revealed that gender ( p = 0.022), number of comorbidities ( p = 0.001), dialysis vintage ( p < 0.001), number of pain sites ( p < 0.001), and PTH level ( p < 0.001) were associated with pain severity score. Older patients ( p = 0.049), gender ( p = 0.007), subjects with a number of comorbidities ( p < 0.001), dialysis vintage ( p < 0.001), number of pain sites ( p < 0.001), and level of PTH ( p < 0.001) were significantly associated with pain interference score. Conclusions The subgroups with increased pain severity were female hemodialysis, subjects living with multiple comorbid conditions, those with length dialysis vintage, a high number of painful sites, and increased PTH levels. Assessing and reducing pain intensity, pain interference, and its factors must be a priority for healthcare providers to manage pain and improve health-related quality of life.